MODEL PENGUKURAN KEPUASAN KERJA DAN PENINGKATAN KINERJA (STUDI KASUS PADA STAF PENGAJAR POLITEKNIK NEGERI LHOKSEUMAWE) - Said Herry Syafrizal; Rusydi Rusydi; Nursyidah Nursyidah; Hamdani Hamdani (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
This study examines the effect of empowerment, self-efficacy and organizational climate on job satisfaction and performance Lhokseumawe State Polytechnic teaching staff as well as review the mediating effect of job satisfaction . The analytical tool used is path analysis (path analysis) by SEM ( structural equation modeling) using Amos , 20. The results showed that each variable empowerment, self-efficacy and organizational climate positive and significant impact on job satisfaction and performance . Job satisfaction positive and significant effect on the performance of teaching staff . as well as job satisfaction variables mediating variables influence empowerment, self-efficacy and organizational climate on the performance of the teaching staff at the Polytechnic of Lhokseumawe Keywords : Empowerment, Self Efficacy, Organizational Climate, Job Satisfaction, Performance